The Psychological Ecology of Academic Flow: Thriving Amidst Limitations in Remote Indonesian Schools - Hidayah, Nurul; Anwar, Alim Akbar; Siglos, Caressa Lynn A. (Jurnal Pendidikan Progresif, 2025)
The Psychological Ecology of Academic Flow: Thriving Amidst Limitations in Remote Indonesian Schools. Objectives: The psychological state in which students experience optimal learning performance is called academic flow, characterized by focus (absorption), enjoyment, and intrinsic motivation. Senior high school students from remote areas need a flow experience because it affects their academic performance and happiness. This research aimed to understand the psychological dynamics and factors that influence students' experiences of flow. Methods: The study used a qualitative phenomenological approach. Six senior high school students from remote areas with the highest academic rank in their class were selected using criterion sampling. The data collection methods used were focus group discussions. Data analysis was conducted using content analysis, and research trustworthiness was ensured using member checks and peer debriefing. Findings: Academic flow in students from remote areas originates from meaningful easiness, well-being in learning, externally conditioned concentration, relational meaning in learning, time perception distortion, satisfaction in transferring knowledge, convergence of internal and external motivation, and the teacher's recognition as a catalyst for engagement. The transformation from limitations to access, moderate challenge learning model, and social support contribute to the emergence of flow in students. Conclusion:  The academic flow of high school students from remote areas is a psychological ecology formed from the interaction between emotional-social scaffolding of teachers and the cognitive-affective regulation of students, where optimal learning occurs when the learning process is experienced as a meaningful collective journey, supported by psychological safety, and strengthened by social appreciation that affirms the students' self-worth as learners. The implications of this finding are the importance for high school teachers from remote areas to build a learning ecosystem that integrates emotional scaffolding, recognition of the learning process, and the design of structured yet accessible challenges, thus creating conditions for the emergence of deep and meaningful learning engagement. Keywords: academic flow, psychological ecology, remote school.